Two missense mutations in KCNQ1 cause pituitary hormone deficiency and maternally inherited gingival fibromatosis. Issue 1 (December 2017) - Tommiska, Johanna; Känsäkoski, Johanna; Skibsbye, Lasse; Vaaralahti, Kirsi; Liu, Xiaonan; Lodge, Emily; Tang, Chuyi; Yuan, Lei; Fagerholm, Rainer; Kanters, Jørgen; Lahermo, Päivi; Kaunisto, Mari; et al.
Abstract Familial growth hormone deficiency provides an opportunity to identify new genetic causes of short stature. Here we combine linkage analysis with whole-genome resequencing in patients with growth hormone deficiency and maternally inherited gingival fibromatosis. We report that patients from three unrelated families harbor either of two missense mutations, c.347G>T p.(Arg116Leu) or c.1106C>T p.(Pro369Leu), inKCNQ1, a gene previously implicated in the long QT interval syndrome.Kcnq1 is expressed in hypothalamic GHRH neurons and pituitary somatotropes. Co-expressing KCNQ1 with the KCNE2 β-subunit shows that both KCNQ1 mutants increase current levels in patch clamp analyses and are associated with reduced pituitary hormone secretion from AtT-20 cells. In conclusion, our results reveal a role for the KCNQ1 potassium channel in the regulation of human growth, and show that growth hormone deficiency associated with maternally inherited gingival fibromatosis is an allelic disorder with cardiac arrhythmia syndromes caused byKCNQ1 mutations. Growth retardation is most commonly caused by genetic defects in the growth hormone pathway. Here, in families with growth retardation and gingival fibromatosis, the authors identify mutations in the potassium channel geneKCNQ1 that cause electrophysiological aberrations and altered ACTH secretion in vitro.